The New Algerian Arabic Novel: Formation Struggles, Experimental Stakes, and Characteristics - Souad, Hamadoun; Belkacem, Malkia (Journal of Ecohumanism, 2024)
This study examines the evolution of the new Algerian Arabic novel in light of its historical, political, and social contexts. It explores how this literary form emerged as a response to transformations in Algerian society, particularly in the wake of pivotal events such as the June 1967 defeat, the October 1988 uprising, and the "Black Decade" of the 1990s. Influenced by both the Western "Nouveau Roman" and pioneering Arabic novelists from Egypt and the Levant, Algerian novelists adopted innovative narrative techniques including fragmentation, autofiction, myth, metanarration, and polyphony. While the early Algerian Arabic novels often aligned with ideological and state-driven narratives, later generations sought a more nuanced and introspective representation of the Algerian condition. This paper identifies the aesthetic, philosophical, and technical features that distinguish the new Algerian Arabic novel and evaluates its contribution to Arabic and global literary movements. The study concludes that despite moments of artistic decline or mimicry, the new Algerian Arabic novel has produced unique and influential voices that reflect the deep and complex reality of Algerian society.